2019
DOI: 10.1088/1742-6596/1280/3/032052
|View full text |Cite
|
Sign up to set email alerts
|

Using argument-driven inquiry to promote students’ concept mastery in learning global warming

Abstract: The process of learning science in some schools is still in the form of direct transfer from teacher to student. The learning process will be meaningful if the students involved and explore more in building a concept. The aim of this study is to investigate the impact of Argument-Driven Inquiry on students’ concept in learning global warming. The method that is used in this research was quasi-experiment. The study used two classes with one experimental group that used Argument-Driven Inquiry and one control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…Quizizz merupakan salah satu platform yang dapat dimanfaatkan oleh guru untuk membuat media pembelajaran fisika interaktif. Quizizz berbentuk aplikasi game edukasi yang bersifat naratif dan fleksibel, selain sebagai sarana penyampaian materi pembelajaran juga dapat digunakan sebagai media evaluasi pembelajaran yang menarik dan menyenangkan (Elnovreny, 2021;Salsabila et al, 2019). Selain berupa aplikasi, pengguna dapat mengaksesnya melalui situs web Quizizz tanpa perlu mendownload berbentuk aplikasi.…”
Section: Pendahuluanunclassified
“…Quizizz merupakan salah satu platform yang dapat dimanfaatkan oleh guru untuk membuat media pembelajaran fisika interaktif. Quizizz berbentuk aplikasi game edukasi yang bersifat naratif dan fleksibel, selain sebagai sarana penyampaian materi pembelajaran juga dapat digunakan sebagai media evaluasi pembelajaran yang menarik dan menyenangkan (Elnovreny, 2021;Salsabila et al, 2019). Selain berupa aplikasi, pengguna dapat mengaksesnya melalui situs web Quizizz tanpa perlu mendownload berbentuk aplikasi.…”
Section: Pendahuluanunclassified
“…Many studies on physics concept mastery have been undertaken using learning models and approaches. Several previous studies showed that predictobserve-explain (POE) learning strategies (Furqani, Feranie and Winarno 2018), argument-driven inquiry (Salsabila et al 2019), three-dimensional solid object motion mechanics (Hartini et al 2020), and guided inquiry-based practical manual (Andriani, Sunyono and Abdurrahman 2018) effectively improve students' concept mastery. Good concept mastery is also influenced by authentic assessment learning models.…”
Section: Introductionmentioning
confidence: 99%
“…Students' concept mastery can be improved based on students' experience in solving challenges. In previous studies, the improvement in concept mastery was analyzed through the value of N-gain (Andriani, Sunyono and Abdurrahman 2018;Furqani, Feranie and Winarno 2018;Pratiwi, Rochintaniawati and Agustin 2018;Wandari, Wijaya and Agustin, 2018;Andanawarih, Diana and Amprasto 2019;Salsabila et al 2019;Sani, Rochintaniawati and Winarno 2019). The progress in concept mastery was also analyzed using ANOVA test (Satriawan, Liliasari and Setiawan 2019;Amalia et al 2020) and t-test (Setiawan, Sopandi and Hartati 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mastery not only forms the bedrock for advanced cognitive abilities but also fosters effective communication, idea classification, critical thinking, and overall cognitive enhancement (Oktaviani et al, 2017;Sari et al, 2018;Sofiuddin et al, 2018). Moreover, it underpins the capacity for engaging in scientific discourse and constructing persuasive arguments based on sound conceptual frameworks (Amin & Corebima, 2016;Amiroh & Admoko, 2020;Chen & She, 2012;Demircioğlu & Ucar, 2012;Eliana & Admoko, 2020;Kim, 2015;Marhamah et al, 2017;Puspitaningrum et al, 2018;Salsabila et al, 2019;Supeno et al, 2015;Wardani et al, 2018). Therefore, by attaining mastery of fundamental concepts, students not only acquire diverse high-level skills but also cultivate the ability to construct scientifically grounded arguments employing accurate conceptual frameworks.…”
mentioning
confidence: 99%